Electrolytic decolorization of color-simulated textile wastewater - Malenab, Roy Alvin J. (Animo Repository, 2024)
The indirect electro-oxidation of color-simulated textile wastewater was investigated at different operating currents and different amounts of additional NaCl.Results showed that complete to near complete decolorization could be achieved by the process. The rate of color removal as well as the time to achieve more than 95% decolorization was dependent on the operating current and amount of NaCl added. In general, an increase in current (A) resulted to an increase in the rate of color removal up to a saturated condition depending on the initial chloride ion concentration. Increasing the amount of chloride ion (as NaCl) in the color-stimulated wastewater improved the rate of color removal and decreased the required voltage due to the increase in conductivity. No considerable change in pH was observed.Two values of charge dose were evaluated for the process; 2.27 coulomb/mg color removed for the first stage and 29.46 coulomb/mg color removed for the second stage. This is du to the diversity of the dye molecules dissolved in the simulated effluent. An optimum ratio of the amount of NaCl to be added for every ampere of operating current was calculated to be 0.35 g NaCl/A. This factor, together with the charge dose could be used as practical scale up and operating factors for the process..